Wireless sensor networks propagation study in mixed-crop farming - Harun, A.; Latifah Munirah, Kamarudin; Ammar, Zakaria; Ndzi, D. L.; Ali Yeon, Md Shakaff, Prof. Dr.; Mahmad Nor, Jaafar, Prof. Madya Dr. (Universiti Malaysia Perlis (UniMAP), 2012)
International Conference on Man Machine Systems (ICoMMS 2012) organized by School of Mechatronic Engineering, co-organized by The Institute of Engineer, Malaysia (IEM) and Society of Engineering Education Malaysia, 27th - 28th February 2012 at Bayview Beach Resort, Penang, Malaysia.